Comparative Studies on Chemical Composition, Phenolic Compounds and Antioxidant Activities of Brown and White Perilla (Perilla frutescens) Seeds - Sikeret Kongkeaw (Science Faculty of Chiang Mai University, 2019)
Chemical composition, phenolic compounds and antioxidant activities of brown perilla and white perilla seeds were comparatively studied. Brown perilla seed had higher protein, fat, ash and crude fiber contents than those of white perilla seed (p<0.05). Additionally, brown perilla seed contained greater contents of Ca, Mg, and P than those of white perilla seed (p<0.05). However, no difference in Fe content was found in both seeds (p>0.05). Brown perilla seed was rich in polyunsaturated fatty acid, in particular g-linolenic acid and a-linolenic acid. The most abundant of b-carotene and a-tocopherol was found in brown perilla seed. Higher total phenolic, total flavonoid, and total flavonol contents together with higher 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2’-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS)-radical scavenging activities as well as a greater reducing capacity were observed in brown perilla seed extract (p<0.05). Therefore, brown perilla seed can be a good source of both macro- and micro-nutrients with phytochemical antioxidant activity.